Medição e modelagem do efeito pelicular para estudos de fluxo harmônico em sistemas de distribuição de energia elétrica - Silvério, Eduardo Tavares Silvério (2024)
Technical losses occur due to the energy transfer among generating units to the consumers. Therefore, only the fundamental frequency component of voltage and current is considered, in accordance with the regulation enforced on electric power systems. However, load typology has been changing and new technologies, such as semiconductors, emerges. In this scenario, an increase on voltage and current distortion is observed. Consequently, power losses computed through fundamental components are not adequate to represent the real electrical conditions on power systems. In this case a new methodology covering harmonic components should be considered to compute power losses regarding energy transfer. Thus, harmonic distortions have become more intense, due to more non-linear loads connected on power systems, and an increase in power losses have been noted. This may be explained because of the increase in current rms values led by harmonic distortions. Nevertheless, it may also be due to Skin Effect on conductors, where its resistance values are incremented once harmonic currents flows through the conductor. The current body of work aims to model the Skin Effect, in order to reduce the simulation time in harmonic power flow studies, which can take several days, considering a real power distribution network. In addition, this thesis aims to quantify the impact that the Skin Effect has on technical losses in electricity distribution networks. The approach carried out includes analytical development of the phenomenon, electrical resistance measurement methodology, as well as computer simulation with the verification of an increase in regulatory losses through Python in interface with OpenDSS. The results indicate that the proposed methodology is satisfactory, providing a significant reduction in the simulation time and, additionally, produces results faithful to the models traditionally used in harmonic power flow simulation software.